Phyto-Ecological Assessment of Mahakali River, Far-western Nepal - Kunwar, Ripu M; Pyakurel, Pratistha; Burlakoti, Chundamani; Pyakurel, Parakram; Shah, Shree G. (Journal of Natural History Museum, 2018)
An assessment of phyto-ecology and socio-economy of wetlands of Mahakali River system of far-western Nepal was carried through rapid ecological assessments, participatory discussions, transects and quadrat studies, and laboratory analyses to reveal the interactions between physico-chemical characteristics of water and soil, biodiversity and socio-economic regimes. Mahakali river system was flanked by a number of tributaries, steep cliffs, rocks, and was closely associated with riverine and mixed Shorea robusta (Sal) forests, resulting in richness and diversity of habitats and plant species. Vegetation succession was found to conspicuous as transcends farther from river edge, the Phragmites karka was gradually succeeded by Saccharum spontaneum and riverine forest species such as Acacia catechu, Dalbergia sissoo, Bombax ceiba, Eugenia jambolina, Aegle marmelos, etc. A total 140 plant species including 78 ethnomedicinal were inventoried, representing about 27 percent of the district flora. This study serves as a baseline data of phyto-ecological attributes of Mahakali River and can be taken as a reference to investigate the temporal changes in Mahakali River system. J. Nat. Hist. Mus. Vol. 29, 2015, Page: 32-48